2007
DOI: 10.1007/s11064-006-9278-5
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb Immunoreactivity, Protein and mRNA Levels Significantly Increase in the Aged Hippocampus Proper in Gerbils

Abstract: Myb genes are a family of transcription factors and have been implicated in the control of the proliferation and differentiation of normal and transformed cells. c-Myb is the best characterized member of the myb family. In the present study, we investigated age-dependent changes of c-myb immunoreactivity, its protein and mRNA level in the hippocampus proper (CA1-3 regions) at various age stages in gerbils. In the postnatal month 1 (PM 1) group, c-myb immunoreactivity was detected in non-pyramidal neurons of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…Furthermore, inflammation appears to play a central role among the various processes that have been associated with brain aging. Moreover, the hippocampus is a brain region essential for intact cognitive abilities and appears to be particularly vulnerable to the aging process [14][15][16][17][18]. Dogs are known to develop a well characterized cognitive deficit syndrome during aging [19][20][21], and age-related changes are observed in the canine brain which is accepted as a model of human brain aging [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inflammation appears to play a central role among the various processes that have been associated with brain aging. Moreover, the hippocampus is a brain region essential for intact cognitive abilities and appears to be particularly vulnerable to the aging process [14][15][16][17][18]. Dogs are known to develop a well characterized cognitive deficit syndrome during aging [19][20][21], and age-related changes are observed in the canine brain which is accepted as a model of human brain aging [19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HSF3 induces the expression of Hsps by binding to c-myb (Tanikawa et al 2001). Recently, it was reported that the c-myb protein and mRNA were increased during the Gerbil hippocampus ageing process (Hwang et al 2007). These phenomena may suggest that elevation of c-myb expression serves anti-apoptosis role in aged cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that c-myb increases the protein level during ageing (Hwang et al 2007). This study examined the role of c-myb in cell survival against oxidative stress in aged HDF cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these findings, the researchers discovered that many of the promoters of differentially methylated genes were enriched with binding sites of transcription factor MYB in samples of patients without known mutations. Interestingly, this transcription factor has been linked to aging [142], as well as to the response to oxidative stress of aged cells [143]. …”
Section: Link To Diseasementioning
confidence: 99%